A DEVELOPMENT OF VON NEUMANN MACHINES WITH ARTIFICAL NEURO-GLIA NETWORK - Rai, Ankush; R, Jagadeesh Kannan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Artificial Neuroâ€“Glia Networks (ANGNs) are upcoming approach in soft computing wherein the effects biological counterpart of artificial glia cells are used to support pattern based growth mechanism in artificial neural network. In this study we present a mathematical model of such ANGNs to build a von neumann machine. This method will properly learn its parameters for increasing the growth of neural network which can be used for solving several scaling problems in computing. Â 